Study in the efficacy of Kushthadi Yoga in Ekakushtha with special reference to Psoriasis- A Comparative Clinical Study” - Nimbhorkar, Ashish U.; Misar, Sadhana; Gaidhane, Shilpa (International Journal of Psychosocial Rehabilitation, 2020)
To evaluate the efficacy of Kushthadi Yoga the management of Ekakushtha with special reference to Psoriasis . In this study,40 patients will be randomly divided into 2 groups(20 in each ).In Group A (Control) - Kushthadi Capsule 500 mg will be administered twice a day with lukewarm water after meal for 30 days along with Kushthadi Ointment and Group B (Experimental) –Placebo Capsule 500 mg will be administered twice a day with lukewarm water after meal for 30 days along with Kushthadi Ointment. Assessement will be recorded on 0,30th and 60th day. Changes will be observed in subjective and objective outcomes. Kushthadi Capsule will be more effective than Placebo Capsule